(In)security in the unscheduled loss of Nasoenteral Catheter in clinical units – ethical and financial damages (Research, Society and Development, 2023)
This study aimed to analyze the cost-quality of care related to the practice of nasoenteral catheter insertion. This is a descriptive, quantitative-qualitative study, which had as its scenario a public hospital located in the State of Rio de Janeiro. Data collection was performed by the resident responsible for this research and by two other resident researchers, through semi-structured interviews with open and closed questions, addressing specific questions about the insertion of the nasoenteral tube, the hospital experience on the subject, its knowledge and its capacity for reflection. The nurse is a professional with technical capacity, and sufficient theoretical knowledge to realize when a procedure is not necessary for the patient, in addition, the practice of performing blind prescription execution that may result in damage to the patient, is punishable and hurts the objective of patient safety. Moreover, even if the procedure does not give physical damage, ethics allows us to understand that there is psychological damage to the patient, and consequently there is a crime. It was identified the need for investment in training aimed at the care indispensable to the procedure of insertion and maintenance of NES in order to provide its professionals with significant knowledge so that through this intervention a reduction in financial cost is achieved.